Correlation Between Parental Knowledge of Oral Health and Dental Caries Incidence Among Preschool Children at Ar-Rahman Foundation Jombang (International Journal of Advanced Health Science and Technology, 2026)
Dental caries remains one of the most prevalent oral health problems among preschool children and continues to pose a significant public health concern, particularly in developing countries. Inadequate parental knowledge of oral and dental health is often considered a contributing factor to the high incidence of early childhood caries. This study aimed to examine the relationship between parental knowledge of oral health and the incidence of dental caries among preschool children attending PAUD and Kindergarten under the Ar-Rahman Foundation in Jombang, Indonesia. A quantitative cross-sectional design was employed involving 39 parents and their preschool-aged children selected using total sampling. Parental knowledge was assessed using a structured questionnaire, while dental caries status in children was evaluated using the def-t (decayed, extracted, and filled teeth) index. Data were analyzed using the Chi-square test with a significance level of α = 0.05. The results indicated that the majority of parents (51.3%) had low levels of oral health knowledge, while only 10.3% demonstrated good knowledge. Dental caries prevalence among preschool children was relatively high, with higher def-t scores more frequently observed among children whose parents had lower knowledge levels. However, statistical analysis revealed no significant association between parental knowledge and the incidence of dental caries (p = 0.286). Despite the absence of a statistically significant relationship, descriptive findings suggested a tendency toward poorer oral health outcomes among children of parents with limited knowledge. In conclusion, parental knowledge alone was not significantly associated with dental caries incidence among preschool children in this study. These findings suggest that dental caries is influenced by multiple factors beyond knowledge, including behavioral practices, dietary patterns, and access to dental care. Comprehensive oral health promotion programs that integrate parental education with practical behavioral interventions are therefore essential to improve early childhood oral health outcomes.